Stock Market Integration with Special Reference to India : A Review of Literature - Agrawal, Pravin Kumar; Nandan, Tanuj; Singh, Ashutosh Pratap (Indian Journal of Research in Capital Markets, 2020)
The main theme of this study was to provide the available existing comprehensive literature on stock market integration with special reference to India in a summarized form so that investors can quickly access the present integration status of India with existing developing and developed countries. Data were collected from various sources since 1997 – 2015 and was analyzed in such a way that it might helpful to investors, researchers, foreign portfolio investors, academicians, etc. It was found that after 2008, integration status of the Indian stock market with developing and developed nations had increased. Policy makers will be duly benefited by such financial integrations while framing suitable policies for the economy, and while addressing issues related to crises moving from other markets to their own domestic market. Various financial institutions, foreign portfolio investments (FPIs), foreign institutional investors (FIIs), and mutual fund companies optimized their returns by investing in different countries. Such global investors could make more rational decisions by studying the strength of interdependencies and interlinkages among stock markets of different countries. In the last few years, investments made by FIIs or foreign investors were of significant quantum in India ; so, there is a need to check whether they would be benefited by investing in India.